1974
DOI: 10.1104/pp.54.4.624
|View full text |Cite
|
Sign up to set email alerts
|

Sterol Molecular Modifications Influencing Membrane Permeability

Abstract: Various sterols and related steroids were tested for their ability to influence ethanol-induced electrolyte leakage fron Hordeunm vulgare roots. Cholesterol had the greatest influence and, depending on concentration, it stimulated or inhibited the loss of electrolyte. Cholesterol, however, was ineffective if the roots were pretreated with ethanol. These data suggest that sterols protect rather than restore membrane structure. First, modifications in the cholesterol perhydrocyclopentanophenanthrene ring system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…Similarly, the effects of stigmasterol and sitosterol on the water permeability of monogalactosyldiglyceride bilayers are distinguishable from those of cholesterol (11). In membrane systems, campesterol, sitosterol, and stigmasterol have been shown to be less effective than cholesterol in protecting membranes from ethanol-induced damage (13).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Similarly, the effects of stigmasterol and sitosterol on the water permeability of monogalactosyldiglyceride bilayers are distinguishable from those of cholesterol (11). In membrane systems, campesterol, sitosterol, and stigmasterol have been shown to be less effective than cholesterol in protecting membranes from ethanol-induced damage (13).…”
Section: Discussionmentioning
confidence: 96%
“…Studies with artificial membrane systems have demonstrated that three properties of the sterol molecule allow it to intercalate into phospholipid bilayers: a planar ring structure, a side chain at carbon 17, and a 3 ,B-hydroxyl group (7,13 acid side chains (7). The plant sterols sitosterol, stigmasterol, and campesterol differ structurally from cholesterol only in respect of the side chain on C17.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ratio of FS:BS has a much greater effect on membrane permeability than the composition of the FS fraction and, therefore, any significant decrease in FS:BS ratio results in cell injury. The proposed overall hypothesis is based on the notion that 03 alters membrane permeability (2) and that sterols, an important lipid component ofmembranes, plays a key part in the stabilization of membranes (4,5).…”
Section: Grunwald and Endressmentioning
confidence: 99%
“…Sterols play an important structural role in the stabilization of membranes of vascular plants (8), and it has been suggested that changes in sterols alter cell permeability (8,9). The amount of sterol and the composition of the sterol mixture are modified as a plant goes through its various stages of development or is exposed to changing environmental conditions (6,9).…”
mentioning
confidence: 99%